A CRITICAL STUDY ON LIBRARY USER’S AWARENESS AND SATISFACTION LEVEL OF E-RESOURCES - Biswas, Nibhas; Kishore, Nand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
There is a growing consensus among academics that electronic resources are crucial, essential, and highly advantageous. The significant technological advancements, particularly in the last decade of the twentieth century, have led to the rapid emergence of electronic resources, which are gradually displacing traditional print resources. Librarians need to stay up-to-date on the latest services and acquire new skills to meet the demands of the digital world. This research looks at how well users are aware of and make use of e-resources. Using a simple random sample procedure, 150 completed questionnaires were collected from students using the library. The survey was designed with quantitative data. The results indicate a need for improved outreach by library staff, enhanced infrastructure, and targeted orientation programs to better support students in accessing and utilizing e-resources effectively.